Review of the mangrove conservation behaviour from environmental psychological perspectives / Nurul Asyqin Ramli, Gobi Krishna and Noor Aiman - Ramli, Nurul Asyqin; Krishna, Gobi; Aiman, Noor (Universiti Teknologi MARA, Perak, 2023)
Despite the mangrove's ecosystem contributing to mitigating the effects of climate change, its significance is unknown, putting it at risk of extinction. This has contributed to a number of mangrove rehabilitation programs. However, ensuring the long-term efficiency of the conservation programs needs the involvement of the local community. Therefore, this paper aims to understand the local community mangrove conservation behaviour guided by the psychological factor that influences people's behaviour. This research is carried out by adopting qualitative techniques through Focus Group Discussion (FGD) which involved local communities from Kg. Tg. Keramat, Kuala Selangor. Results showed that the local community nearby the mangrove forest has a positive intention and attitude towards mangrove conservation based on the five themes assigned through the FGD. The five main themes are perception, intention, attitude, perceived behavioural control, and personal norm. Among the local community, perceived behavioural control has the most positive effects on mangrove conservation. However, because of the lack of conservation activities involving the local community, there were no community empowerment and enforcement from the top management upon receiving activity reports which significantly changed their intention towards mangrove conservation. From the result, it can be concluded that people that live nearby the mangrove forest will